Microextração Dispersiva em Fase Sólida (D-µSPE) para extração de parabenos em cosméticos - Fukuyama, Conny Wara Terán (Universidade Federal de São Carlos, 2025)
Parabens are a class of preservatives widely used in cosmetics, pharmaceuticals, and food products due to their antimicrobial properties and cost-effectiveness. Recently studies highlighted potential harmful effects associated with these preservatives, including hormonal dysregulation and increase risk of cancer and, in infants, parabens are associated with skin reactions and immunological dysregulation. Graphene oxide-based sorbents have been used on extraction of cosmetic ingredients and graphene oxide (GO) modification can enhance sorbents selectivity. This study developed and optimized an analytical method for the detection and quantification of parabens (methylparaben, ethylparaben, propylparaben and butylparaben) in cosmetic samples (cleanser, moisturizer and sunscreen) using dispersive solid-phase microextraction (D-μSPE) coupled with high-performance liquid chromatography with ultraviolet and visible light detection (HPLC-UV/Vis) and mass spectrometry (HPLC-MS/MS). GO-based sorbents modified with ionic liquid, as well as commercial sorbents, were evaluated by dispersive solid-phase microextraction (D-μSPE) and microextraction by packed sorbent (MEPS). The sorbent functionalized with zwitterionic liquid, ViImC4S@GO, exhibited superior extraction capacity compared to other sorbents. A methodology was developed using dispersive solid-phase microextraction (D-μSPE), based on the parameters such as sorbent amount, desorption solvent, solvent volume, extraction time, elution time, and sample volume; and method performance was assessed through figures of merit including selectivity, limit of detection (LOD), limit of quantification (LOQ), linearity, precision, accuracy, and matrix effect. Finally, the developed method was applied to real samples.
Dispersive Micro-Solid Phase Extraction (D-µSPE) of parabens in cosmetics
Keywords: Parabenos; Cosméticos; Óxido de grafeno (GO) modificado; Microextração dispersiva em fase sólida (D-µSPE); Microextração por sorvente empacotado (MEPS); CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA; CIENCIAS DA SAUDE::FARMACIA; CIENCIAS DA SAUDE::FARMACIA::FARMACOTECNIA; 3. Saúde e Bem-Estar